SIKAP DAN PERILAKU KONSUMEN TERHADAP NATIVE ADVERTISING - Siti Aisyah (AT-TAWASSUTH: Jurnal Ekonomi Islam, 2020)
The marketing strategy continues to develop. Internet advertising is commonly referred to as e-marketing. Various e-marketing strategies can be done now, for example online advertising. Advertising that used to be offline is now utilizing the internet. One of the formats for online advertising is native ad. Native advertising is a digital advertising format that is still relatively new for online advertising. This study aims to explain how native advertising is used and see how consumers' attitudes towards evaluating native ads. It is recommended to see more than where the original ad can be effectively approved according to marketing objectives. This research uses descriptive analysis technique with random sampling data collection techniques to 420 respondents online. Obtained results from native advertisements that are supported and able to produce positive attitudes and behaviors that benefit marketers or ad owners. Respond to native ads that can provide good information, fun, useful, credible, and do not disturb.